A specialist leukaemia/lymphoma registry in the UK. Part 1: Incidence and geographical distribution of Hodgkin's disease. Leukaemia Research Fund Data Collection Study Group. - McKinney, P. A. (Nature Publishing Group, 1989)
This paper describes the epidemiology of Hodgkin's disease occurring in parts of the United Kingdom between 1984 and 1986. The cases were carefully diagnosed and the data rigorously cross-checked as part of the larger Leukaemia Research Fund Data Collection Survey of all lymphoid and haematogenous malignancies. The age-specific rates show the lack of an older adult second peak. Spatial variation is examined in some detail. At county and district levels there is little heterogeneity in the distribution of cases. However, at the electoral ward level there were real differences for the younger age group (0-34).